An unconventional path to greater social-communication skills and independence for an adolescent on the autism spectrum. (October 2018) - Trembath, David; Bala, Rachel J; Tamblyn, Joanne; Westerveld, Marleen F
Background: In 2015, a father took his 14-year-old son who is on the autism spectrum on a six-month journey aimed to develop his son's social-communication and independent living skills. The duo travelled across 10 countries, meeting people and practising these skills. This study examined their goals, motivations for, and outcomes of the journey. Method: We used intrinsic case study methodology with mixed methods, including interviews with parents and professionals; analyses of filmed interactions between the son, his father and strangers during the journey; and descriptive analysis of parent-reported changes in their son's participation at home, school and in the community using the Participation and Environment Measure – Children and Youth. Results: Qualitative analysis of the interviews with parents and professionals revealed a set of insightful goals and motivations, focusing on creating an optimal environment for the son's development. Parents reported increases in their son's social-communication and independent living skills, but also unexpected changes in his perspective and self-belief. The former findings were consistent with those arising from video analysis, whereby social-pragmatic skills critical to good conversations (staying on topic, body position, eye contact) all increased over the course of the journey, while abrupt topic changes and conversational prompts reduced. Participation and inclusion across home, school and community settings all increased over the same period. Conclusion: While this study makes no claims regarding causation, the findings indicate that the journey was associated with positive changes for the son and his parents, leading to greater expectations for, and progress towards, independence following the journey. Implications of the findings for supporting young people on the autism spectrum in regular community settings are discussed.